Refractive Indices of Solids - Batsanov, Stepan S.; Ruchkin, Evgeny D.; Poroshina, Inga A.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book highlights the basics of crystal optics methods and refractive index (RI) measurement techniques in various solids, as well as their scientific and technological applications. In addition to new techniques for cases when traditional techniques are impractical, such as for highly refracting powders, anomalous dispersion of light in the studied solid, or for colloids, it also describes conventional methods of RI measurement.
Anisotropy, dispersion, theory, effect of structure -- Anisotropy, dispersion, theory, effect of structure -- Chemical bonding and refractive indices -- Refractive indices of elements and binary compounds -- Refractive indices of ternary or complex halides and oxides -- Refractive indices of silicates and germinates -- Refractive indices of uranium compounds -- Refractive indices of the oxygen-containing salts -- Refractive indices in the coordination compounds of b-elements -- Refractive indices in coordination compounds of a-metals -- Crystallohydrates of simple and complex compounds -- Refractive indices of selected organic compounds.
Keywords: Materials -- Analysis; Spectrum analysis; Mineralogy; Materials; Characterization and Analytical Technique; Spectroscopy; Mineralogy; Materials Engineering